IMPLEMENTING MOBILE AGENT FOR LOCATION-BASED PRINTER SERVICES - Rendy Eka Saputra; Sri Wahjuni (Faculty of Computer Science - Universitas Indonesia, 2012)
Most devices in ubiquitous network environment have limited memory and processing power, thus they can’t provide all services even when in suitable locations. Mobile agent technology could be implemented to improve resource efficiency. The goal of this paper is to implement mobile agent technology for location-based printer service. The system consists of four parts: (1) mobile agent server, (2) location-based service server, (3) printer service, (4) client. It is observed that mobile agent offers many advantages for ubiquitous and mobile computing settings. Perangkat dalam lingkungan ubiquitous memiliki memori dan daya proses yang terbatas, sehingga mereka tidak dapat menyediakan layanan secara utuh bahkan dalam lokasi yang tepat sekalipun.Teknologi mobile agent dapat diterapkan untuk meningkatkan efisiensi sumber daya. Tujuan dari paper ini adalah untuk melihat penerapan teknologi mobile agent pada lokasi berbasis layanan printer. Sistem ini terdiri dari empat bagian: (1) mobile agent server, (2) lokasi yang berbasiskan layanan server, (3) layanan printer, (4) klien. Hal ini menunjukkan bahwa mobile agent menawarkan banyak keuntungan untuk pengaturan komputasi ubiquitous dan mobile.